2018
DOI: 10.1371/journal.pone.0195502
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid compound apigenin prevents colonic inflammation and motor dysfunctions associated with high fat diet-induced obesity

Abstract: Background and purposeApigenin can exert beneficial actions in the prevention of obesity. However, its putative action on obesity-associated bowel motor dysfunctions is unknown. This study examined the effects of apigenin on colonic inflammatory and motor abnormalities in a mouse model of diet-induced obesity.Experimental approachMale C57BL/6J mice were fed with standard diet (SD) or high-fat diet (HFD). SD or HFD mice were treated with apigenin (10 mg/Kg/day). After 8 weeks, body and epididymal fat weight, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…Conversely, adipocyte hypertrophy is also accompanied by an opposite downregulation of anti-inflammatory and insulin-sensitizing adipokines, such as adiponectin, and impaired antioxidant defense. The increased oxidative stress and altered pattern of secretory products by adipocytes participate in the establishment of an autocrine/paracrine loop, with further adipocyte and macrophage pro-inflammatory activation and derangement, as well as of an "endocrine" signaling, propagating AT dysfunction to distant metabolic and vascular organs [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, adipocyte hypertrophy is also accompanied by an opposite downregulation of anti-inflammatory and insulin-sensitizing adipokines, such as adiponectin, and impaired antioxidant defense. The increased oxidative stress and altered pattern of secretory products by adipocytes participate in the establishment of an autocrine/paracrine loop, with further adipocyte and macrophage pro-inflammatory activation and derangement, as well as of an "endocrine" signaling, propagating AT dysfunction to distant metabolic and vascular organs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols from several food sources have been increasingly found to favorably affect AT physiology [38], and their modes of action include interaction with cell signaling pathways, modulation of transcription factors activity and gene expression, but also the post-transcriptional regulation of genes via modulation of miRNAs expression [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that natural flavonoids have good anti-inflammatory activities. For example, apigenin can prevent colon inflammation and motor dysfunction in obese mice induced by a high-fat diet [40]. Naringin can reduce the cell viability, fat content, and inflammatory response of breast tumor cells in ovariectomized obese mice [41].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids comprise a large group of polyphenolic compounds that arise naturally in plants (Gentile et al, ). Earlier studies have reported that these compounds have a wide variety of therapeutic properties such as anti‐inflammatory, antioxidant, and antihypercholesterolemic activities (Elliot‐Middleton, Kandaswami, & Theoharides, ).…”
Section: Introductionmentioning
confidence: 99%